Progress toward pharmacotherapies for cannabis-use disorder: an evidence-based review - Copel; J; Pokorski I (Dove Medical Press, 2016)
Jan Copeland, Izabella Pokorski UNSW Medicine, University of New South Wales, Sydney, NSW, Australia Abstract: Cannabis is the most widely used and variably regulated drug in the world, with increasing trends of use being reported in the US, Australia, Asia, and Africa. Evidence has shown a decrease in the age of commencement of cannabis use in some developed countries and a prolongation of risk of initiation to cannabis use beyond adolescence among more recent users. Cannabis use is associated with numerous health risks and long-term morbidity, as well as risk of developing cannabis-use disorders. Cannabis users infrequently seek professional treatment, and normally do so after a decade of use. Cannabis-use disorders are currently treated using a selection of psychosocial interventions. Severity of withdrawal is a factor that increases the risk of relapse, and is the target of pharmacotherapy studies. Currently, there is no approved pharmacotherapy for cannabis-use disorders. A number of approaches have been examined, and trials are continuing to find a safe and effective medication with little abuse liability. Keywords: marijuana, treatment, intervention, withdrawal, cannabinoid